Effect of aging on reclaimed asphalt pavement and rejuvenators. Issue 1 (1st July 2022) - Aeron, P; Aggarwal, P
Abstract: Reclaimed Asphalt Pavement (RAP) material primarily consists of extracted asphalt concretes from the existing road infrastructure. It comprises 2 major non-renewable resources, i.e., aggregates and bituminous binder and their conscious use can ensure the sustainability of bituminous pavement construction. In this study, more focus is given to the asphalt binder, which is extracted from RAP. It has been tried to replace more and more new virgin binders with recycled RAP binders. But to counteract the higher stiffness of the RAP binder, it is rejuvenated to achieve strength higher or equivalent to the target binder. To have confidence in the efficacy of the RAP binder and rejuvenator in unaged and aged conditions, different combinations of blends are made and tested in aged as well as unaged conditions. In this study, Two RAP sources with and without virgin binder are rejuvenated with two rejuvenators. Physio-rheological tastings are done on each same. Based on achieved results aging index of all the blends is found. These results authenticate the aging properties of RAP binder as well as rejuvenators.